PENYELESAIAN SENGKETA TANAH GARAPAN PERKEBUNAN DI KEBUN SEI PUTIH PTPN III DALAM PERSFEKTIF HUKUM - Kusbianto; Azmiati Zuliah; Muhammad Asri Pulungan (Fakultas Hukum Universitas Kristen Indonesia, 2020)
The conflict in the farming sector, for example, was the problems of cultivated land, which tendedto cause horizontal conflict between the plantation and the cultivator communities. The disputeclaimed that each side had a right to their land, a land dispute in this study between the PTPN IIIand the self-successful then-peasant community (KTSM) Sei Galang, because of a lawsuit by agroup of farmers demanding legal action against a law that had ruined the land area by 345.56ha.The problem of this study is to find out how the plantation companies are solving the demandsof the plantation area and what the society is demanding is to cultivate the plantation area indispute in the rights area for business by using normative methods of study through courtdecisions and field or sociological studies of a qualitative type of research. The result of thisstudy has shown that the demands of the parties to the PTPN (III) of Gartu land are not upheldon the merit of credentials or credentials authentic. The rights/proofs that the people submittedby the people were simply photocopied that could not be investigated. The tendency to thecommunity's demands in the white Sei garden was brewed to the settlement, which was unclear towhat level of court process, so the society's demands were unfounded. Sugata hoped that thesolution would be a non-litigation approach in settlement of the land dispute existing in the PTPNIII, particularly the plantations in North Sumatra. Keywords: Dispute Settlement, Arable Land, PTPN III Sei Putih Plantation.